2015
DOI: 10.1515/hepo-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing potential of Capparis spinosa against cutaneous wounds infected by Escherichia coli in a rat model

Abstract: S u m m a r yWound infection has become a major medical problem in recent years. This study was conducted to evaluate the healing activity of Capparis spinosa against surgical wounds infected by Escherichia coli. Twenty male rats were divided into two groups. Excisions were created surgically on the animals' skin and then infected with E . coli. Group 1 was treated with C . spinosa while Group 2 was untreated. Wound biopsy specimens were collected on days 5, 10 and 16 and analyzed. Results showed that the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Counting the number of the inflammatory cells in five field Using light microscope with square grid in one eyepiece of the microscope; cells were counted under (power x40) lens, and then the mean number of cells was recorded for all healing periods [8]. The results showed that the mean values decreased with time in each studied group, the highest values were recorded in group C after 3 days and lowest values in group A in 7 days healing period, these findings are also demonstrated in Figure (13).…”
Section: Inflammatory Cell Parametermentioning
confidence: 68%
See 1 more Smart Citation
“…Counting the number of the inflammatory cells in five field Using light microscope with square grid in one eyepiece of the microscope; cells were counted under (power x40) lens, and then the mean number of cells was recorded for all healing periods [8]. The results showed that the mean values decreased with time in each studied group, the highest values were recorded in group C after 3 days and lowest values in group A in 7 days healing period, these findings are also demonstrated in Figure (13).…”
Section: Inflammatory Cell Parametermentioning
confidence: 68%
“…Plant extracts are potential agents for wound healing and are mainly favored due to their extensive accessibility, non-toxicity, absence of unwanted side effects and their efficiency as crude preparations. A medicinal agent chosen for wound healing must enhance at least one stage of the healing process without any side effects [13]. Capparis spinosa is a multi-purpose plant that contains a variety of chemically active compounds.…”
Section: Discussionmentioning
confidence: 99%
“…These results obtained in the present study were in accordance with the results of previous wound healing studies performed using Capri extract. [ 10 , 15 , 16 ] To investigate the wound healing activity of C. ovata var. palaestina fruit extract in mice, C. ovata var.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Herbal products are potential agents for wound healing, which are highly preferred because of their widespread availability, non-toxicity, lack of undesirable side effects, and effectiveness as raw preparations. [ 10 ] Over recent decades, there has been increasing interest in fruits and vegetables, rich in polyphenols, which contribute to human health. [ 11 ] Polyphenols have been shown to have some potential beneficial effects on human health.…”
Section: Introductionmentioning
confidence: 99%